N. M. Nikolsky and the birth of a peripheral Soviet historiography of antiquity - Krikh, Sergey B. (Journal of the Belarusian State University. History, 2017)
The article concentrated on the problem of the late stage of creative activity N. M. Nikolsky in close relation with history of the genesis the periphery in the Soviet historiography of the Ancient world. Author analyzed the process of creation the new collective sourcebook in ancient history for the pedagogical universities from 1947 to 1952 (when it was printed) and reaction of the Soviet historians on this publication. Author suggests that Nikolsky’s fight for his specific interpretation of oriental history and his critic of Struve’s conception didn’t work in the way, which Nikolsky was counting, but had anothereffect: it contributed to formation of periphery in Soviet historiography of an Ancient world.
Keywords: Soviet historiography; history of Ancient world; stalinism